2020
DOI: 10.1002/bco2.32
|View full text |Cite
|
Sign up to set email alerts
|

Single‐fraction image‐guided robotic radiosurgery efficiently controls local prostate cancer recurrence after radical prostatectomy

Abstract: Purpose To assess the therapeutic potential of single‐fraction robotic stereotactic ablative body radiotherapy (SABR) in patients with locally recurrent prostate cancer (PC) after radical prostatectomy (RP). Materials and methods We included 35 patients with biochemical failure after RP with single‐site local recurrence in the prostate bed diagnosed by PSMA PET/CT. About 20/35 pts had previously received post‐surgical adjuvant radiation therapy. High‐resolution multiparametric magnetic resonance imaging (mpMRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Combination therapy of radiation therapy and androgen deprivation therapy (ADT) is considered to be effective for patients with prostate cancer (61). It is reported that this combination has more advantages than surgical therapy.…”
Section: Radiotherapy In Prostate Cancermentioning
confidence: 99%
“…Combination therapy of radiation therapy and androgen deprivation therapy (ADT) is considered to be effective for patients with prostate cancer (61). It is reported that this combination has more advantages than surgical therapy.…”
Section: Radiotherapy In Prostate Cancermentioning
confidence: 99%
“…Many cases of recurrent disease after radical prostatectomy will feature only a rising PSA with no imaging findings. In this study by Spek et al 5 , which includes PSMA PET/CT imaging, patients with a single site of local disease had a single fraction of stereotactic ablative body radiation, and they report a respectable early series of 35 patients with follow‐up to show early tumor control and low toxicity. This may be an interesting direction for recurrent disease—combining advances in both imaging and salvage radiation dosing—see high resolution Figure 1 for treatment planning example.…”
mentioning
confidence: 99%